Spontaneous Goal Inference (SGI). Issue 1 (January 2016) - Moskowitz, Gordon B.; Olcaysoy Okten, Irmak
Abstract: When people learn about or observe the behaviors of others, they tend to make implicit inferences from these behaviors (e.g., Uleman, Saribay, & Gonzalez, 2008). Such inferences are an essential part of a person's ability to understand his/her environment and to prepare appropriate behavior within that environment. In the present paper, we review the conditions under which people are more likely to make implicit goal inferences versus implicit trait inferences. The distinction between these two ways of understanding the behavior we observe has important consequences for how we make predictions about future behavior, set expectations for our interaction partners, and how we choose to behave. It can determine when we stereotype. However, until now, the literature has focused on trait inference as the dominant way perceivers make sense of their environment, with little discussion of inferences concerning a person's goals.